Classification of stomach adenocarcinoma based on fatty acid metabolism-related genes frofiling - Liu, Chunhua; Tao, Yongjun; Lin, Huajian; Lou, Xiqiang; Wu, Simin; Chen, Liping (Frontiers in Molecular Biosciences, 2022)
Background: Fatty acid metabolism (FAM)-related genes play key roles in the occurrence and development of STAD. Although immunotherapy has resulted in a paradigm shift in the treatment of STAD, there is significant heterogeneity in patient response due to the complex TIME. The possible role of FAM-related genes in shaping the TIME remains unclear. Methods: The prognostically relevant FAM-related genes were screened in TCGA-STAD cohort using univariate Cox regression analysis. Consensus grouping of the FAM-related prognostic genes was performed to demarcate the molecular subtypes. The abundance of FAM-related genes in each group was determined by GSEA. A prognostic signature based on seven FAM-related genes was developed and validated to predict the OS of STAD patients using univariate Cox regression, LASSO regression and multivariate Cox regression analyses. ESTIMATE was used to evaluate the stromal score, immune score, ESTIMATE score, and tumor purity of each STAD sample. Results: Thirteen FAM-related genes were significantly correlated with the overall survival outcomes in STAD. Two molecular subtypes, namely group 1 and group 2, were identified by consensus grouping of the FAM-related prognostic genes. Group 2 was significantly correlated with poor prognosis, higher PD-L1 expression and distinct immune cell infiltration. Furthermore, GSEA showed that genes involved in apoptosis and the HCM signaling pathway were enriched in group 2. A prognostic risk score was constructed using 7 FAM-related prognostic genes, which was further established as an independent risk factor for STAD (HR=1.717, 95% CI=1.105-1.240, P<0.001). The patients were classified into the high- and low-risk groups, and those in the high-risk group had higher T stage, tumor grade and immune score. Elevated GGT5 expression was significantly associated with worse OS and DFS, as well as advanced T stage and tumor grade, and increased immune cell infiltration. These results suggest that STAD patients with high GGT5 expression in the tumor tissues may respond to immunotherapy. Conclusion: These FAM-related genes and the corresponding infiltrating immune cells are potential therapeutic targets that warrant further study. Furthermore, GGT5 is a promising marker for predicting the response of STAD patients to immunotherapy.